Discurso e subalternidades: a propaganda eleitoral do campo progressista nas eleições presidenciais brasileiras de 2018 - Ribeiro, Renato Coelho (2019)
The Discourse Theory, by Ernesto Laclau and Chanthal Mouffe, with interlocution by postcolonial and decolonial authors, will guide us through the analysis of the electoral campaigns of the progressive field in the Brazilian presidential elections of 2018. Elections that were marked by the proliferation of antagonisms in the speeches that disputed the discursive field. But what we research is focused on the campaigns of candidates who had an identity in the "progressive field", on the "left wing". What we seek to investigate is precisely whether the “progressist” discourse, in a certain way, ended up reinforcing, to a greater or lesser degree, a subalternization of identities, by reproducing, in their speeches, narratives that seek to conform a essentialism, in a dominant power relationship over races, genders and knowledge. Keywords: Political marketing, Discourse Theory, Postcolonial, Decolonial, Post-Marxism